English - Moreno-Kamińska, Natalie (Polskie Studia Krajobrazowe, 2020)
Cultural routes present the values or elements of cultural heritage. They have been permanently inscribed in the landscape of Poland and Europe, thanks to their potential, in the context of historical memory, protection of tangible and intangible heritage, education, and tourism. They are tools for popularizing and bringing out the ethos and identity of the inhabitants. In the context of the development of cultural tourism and the introduction of new trails to the tourist landscape, it is worth considering the role of the experiences acquired by travelers through overcoming the subsequent stages of the cultural route. Participation in activities prepared by trail organizers plays an important role in enabling visitors and natives to learn about the heritage of a given area or to take root in the traditions of a region or nation. The analysis is based on research concerning the tourist landscape, cultural routes, and the author’s own experiences.